International migration in the age of crisis and globalization : historical and recent experiences - Solimano, Andrés (Cambridge University Press, 2010)
The international mobility of people and elites is a main feature of the global economy of today. Immigration augments the labor force in receiving countries and provides many of the bodies and minds that are essential to any vibrant economy. This book is based on a blend of theory, varied country examples, and rich historical material ranging from the mid-nineteenth century to the early twenty-first century. It discusses the conceptual underpinnings of the push and pull factors of current migration waves and their impacts for development on the source and receiving countries. The analysis reviews the historical context under which various migration experiences have taken place - both in periods of internationalism and nationalism - in order to contribute to debates on the desirability of and tensions and costs involved in the current process of international migration.